Electrospun PCL-based nanofibers Arrabidaea chica Verlot – Pterodon pubescens Benth loaded: synergic effect in fibroblast formation. (3rd September 2020) - Costa Salles, Tais Helena; Volpe-Zanutto, Fabiana; de Oliveira Sousa, Ilza Maria; Machado, Daisy; Zanatta, Ana Caroline; Vilegas, Wagner; Lancellotti, Marcelo; Foglio, Mary Ann; d'Ávila, Marcos Akira
Abstract: The guided tissue regeneration (GTR) technique can be applied in dentistry and other medical specializations, such as orthopedics. In modern dentistry, GTR has been used in periodontics and implantology to treat periodontal defects, to reconstruct lost, damaged and atrophied bone tissue in dental implant procedures, and to preserve alveolar bases after tooth extraction. In order to create and improve new therapies and to develop new biomaterials that restore, improve and prevent aggravation of compromised tissue function, poly (ϵ-caprolactone) (PCL) polymer membranes were obtained by the electrospinning process and were associated with two plant extracts: Pterodon pubescens Benth ( P. pubescens ) and Arrabidaea chica Verlot ( A. chica ) which are characterized by their pharmacological activities of anti-inflammatory and healing actions, respectively. Fiber morphology was analyzed using scanning electron microscopy (SEM), where fiber average diameter was measured from SEM images. Contact angle measurements were performed in order to evaluate the hydrophilicity of electrospun membranes containing vegetal extract. High-performance liquid chromatography was used to evaluate the ability to release active ingredients. Cytotoxicity and cell proliferation assays were performed in vitro on NIH-3T3 cells for 1, 3 and 7 d. Electrospun PCL membranes associated with plant extracts P. pubescens and/or A. chica presented a controlled release profile of the active compounds induced fibroblast formation, suggesting that they are promising and suitable for applications in GTR.